Sustainability Communication in Marine Industry : A content analysis of trade fair materials - Hämäläinen, Mika (My University, 2021)
The purpose of this thesis was to understand the communication of sustainability in marine trade fair materials. The purpose was divided into four research questions: what types of sustainability are present in the trade fair materials, how do firms communicate the corporate brand and the firms' offerings, who are the target groups/stakeholders of sustainability communication and how do the materials communicate the value of sustainability. The context of the thesis, marine industry and trade fairs, was reviewed and the key aspects of marketing communication were determined by processing the body of applicable theories of B2B brands, value and sustainability. The scope of the research's context of marine industry and trade fair materials offered the theoretical and practical gap for conducting this research. Together these parts of the extant theoretical literature provided us with the means to research the physical trade fair materials in a holistic way. The empirical part of this study was conducted by a qualitative content analysis. The theoretical framework, a construct that was crafted from the theoretical body of this research, acted as the primary tool for processing the research materials in the empirical analysis. The key points of theoretical framework were coded into the coding sheet and content analysis was carried out. The results were gathered mainly by reviewing the initial results of content analysis as well as by cross-referencing the materials' qualitative categories and introducing simple logic to the research. The results yielded many interesting elements of sustainability communication in marine industry in each main category of content analysis, which was reported in the results chapter and later discussed in the discussions chapter of the thesis. Sense of sustainability communication in marine industry was made by projecting the research questions with applicable parts of the content analysis. Lastly the conclusions of the research were drawn and reported in managerial and theoretical scope, after which the thesis' limitations and future research prospects were presented. Sustainability communication was identified on every conceivable level of examination within the trade fair materials with varying relevancy depending often on the context of the firm that provided the material. Economic sustainability was the most prevalent, followed by environmental and lastly social sustainability. Furthermore the theoretical level of marketing communication as well as the targeted stakeholder groups seemed to be reliant on the examined firm's contextual factors. The way value propositions were presented in the materials was also examined and it was concluded that soft value propositions are usually a better fit for sustainability communication than hard value propositions.